The effect of home visits and video-based health counseling on mothers' roles in managing stunting among toddlers - Ery Wardanengsih; Byba Melda; Agustin Agustin; Yammar Yammar; Nirmawati Darwis; Susmiati Susmiati; Nurasiah Nurasiah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: One of the families at risk experiencing stunting, namely Mother which has child age toddler or those who are breastfeeding. Age toddler as stages development enough children​ prone to to various attack diseases, including diseases caused by deficiencies​ or excess intake nutrition. Purpose: To analyze the effect of home visits and video-based health counseling on mothers' roles in managing stunting among toddlers. Method: Quasi-experimental design with pre-test and post-test approach. Population study is mother who has toddlers in the Wajo Regency. Samples selected use purposive sampling technique. Data collected use questionnaire structured to measure knowledge, attitudes, and practices mother, and sheet observation to monitor growth children. The interventions provided in the form of visit home and education health video- based. Data analysis was performed using statistical tests in pairs to see difference before and after intervention. Results: Showed a significant improvement in mothers’ knowledge, attitudes, and practices following the intervention. Average scores showed an increase between the pre-test and post-test. Statistical test results showed a p-value < 0.05 for all variables, indicating that the intervention had a significant effect. In addition, there were indicators of improved child growth, such as weight and height. Conclusion: Visit home and education health proven video based effective in increase role mother in stunting management. Intervention This can recommended as a strategy in a child-based stunting prevention program public.